Menerapkan Pola Pendidikan Perjanjian Baru pada Pendidikan Kristiani Masa Kini - Hernawati Husain; Lena Anjarsari Sembiring; Simon Simon (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2021)
According to PISA or Programme for International Student Assessment, the country's education system is relatively low in its achievement index compared to other countries. The education system also includes religious-based education. The focus of this article outlines how the system of educational patterns in the New Testament Period. This topic needs to be studied with the purpose of the description in this article can be a lens for all groups, to improve the pattern of education in the NT in relation to the present especially in the scope of Christian Religious Education. The author conducts a literature review to explain how the educational patterns in the New Testament. The results of the presentation in this article found parents to be the main educators before their children study to the formal level. Students learn the rabbi/or teacher way of life is a culture that has become customary in the new testament education pattern. With students learning the rabbinical way of life, making it easier for students to mentor and apprentices is a pattern of education in the New Testament. The implementation of educational patterns in the New Testament in the present day when all elements synergize with performing their respective roles. ABSTRAKMenurut PISA atau Programme for International Student Assessment sistem Pendidikan tanah air tergolong rendah indeks prestasi nya dibanding dengan negara lain. Sistem Pendidikan itu tentu juga meliputi Pendidikan berbasis keagamaan. Fokus artikel ini menguraikan bagaimana sistem pola kependidikan dalam Masa Perjanjian Baru. Topik ini perlu dikaji dengan tujuan uraian pada artikel ini dapat menjadi lensa bagi semua golongan, untuk merelevansikan pola kependidikan di PB dalam kaitan masa kini khsusnya dalam lingkup Pendidikan Agama Kristen. Penulis melakukan kajian literatur guna memaparkan bagaimana pola kependidikan di Perjanjian Baru. Hasil dari pemaparan dalam artikel ini ditemukan orang tua menjadi pendidik utama sebelum anak mereka studi ke jenjang formal. Murid mempelajari cara hidup rabi/atau guru adalah budaya yang sudah menjadi kebiasaan dalam pola kependidikan di Perjanjian Baru. Dengan murid mempelajari cara hidup rabi, memudahkan murid di mentoring serta murid magang adalah pola kependidikan dalam PB. Terimplementasinya pola kependidikan dalam PB di masa kini bila semua elemen bersinergi dengan melakukan peran masing-masing.